Exploring the Relationship between Self-Control and Healthy Eating: Do Self-Description as a Healthy Eater and Attached Importance to Healthy Eating Matter? - Paluckaitė, Justina (Socialiniai tyrimai, 2022)
As suggested by previous research, individuals with high self-control report greater autonomous motivation, and the Self-Determination Theory of autonomous motivation implies that exercising self-control should be less necessary, i.e., require lower levels for those having a self-schema in the relevant domain. Based on this, the present study explored whether the healthy eater self-schema status decreases (moderates) the effect of the trait self-control on the healthy eating behavior. In a cross-sectional design, a total of 149 people participated in this research. Results confirmed the role of the healthy eater self-schema status as a moderator. These findings highlighted the effect of the self-description as a healthy eater and one’s perceived importance of healthy eating in the exercising of trait self-control towards healthy food consumption. This study could also be helpful in tailoring future self-control interventions for individuals who have difficulties in exercising self-control toward healthy food consumption.